Skp2-dependent degradation of p27kip1 is essential for cell cycle progression - Kossatz, Uta (Cold Spring Harbor Laboratory Press, 2004)
The activity of the SCF(skp2) E3 ligase is required for the proteolytic turnover of several proteins involved in cell cycle control and transcriptional regulation. Loss of skp2 in the mouse leads to a complex phenotype including changes in cell size and DNA content as well as severe proliferation defects. Here we show that the loss of a single skp2 substrate, namely, the cyclin kinase inhibitor p27kip1, reverts the phenotype of skp2 knockout hepatocytes to normal. By comparing the kinetics of p27 turnover and cell cycle progression in skp2 knockout and p27T187A knock-in mice, we define a short period in G1 in which p27 is able to block the cell cycle after the exit from quiescence. Loss of p27 turnover during this period prevents mitotic division and instead leads to compensatory cell growth.